Organizations' Responsibility in Maintaining the Security of Personal Data posted Online by Romanian Consumers: an Exploratory Analysis of Facebook and Linkedin - Andreea Ionescu; Laurentiu-Dan Anghel; Gheorghe Jinga (Amfiteatru Economic Journal, 2014)
Despite increased consumer concern about the privacy threat posed by new technologies and the Internet as a whole, there is relatively little evidence that people's privacy concerns actually translate into privacy-enhancing behaviors while online. One can say that it is not yet well understood how privacy concerns and trust influence social interactions between consumers within social networking sites. That is why, this article presents an exploratory study of perceptions of trust and privacy concern, along with willingness to share information and develop new relationships within two of the most popular social networking sites in Romania, Facebook and LinkedIn. The research shows that organizations must assume greater responsibility in ensuring consumers' safety who sometime neglect protecting their personal information, otherwise confidential. In this respect, the application of ISO 26000 standard recommendations by organizations would allow them to pass from just good intentions towards consumers to good actions, so that they are truly protected. The information was gathered with the help of an online questionnaire, administered to people over 18 years old. It is a very useful and needed tool for Romanian companies, as it presents the users' point of view, allowing them to find the best and most ethical way to do social data mining or use consumers' private information, disclosed on such sites. It is our strong belief that sometimes companies have to play an active part in helping users protect themselves from actually disclosing too much personal information on social networking sites. The paper begins with a summary of relevant research related to social networking sites. Then, the online survey methodology is described and the results presented, followed by limitations and conclusions.
Keywords: M31; 330; organizations' responsibility; consumers; privacy; protection of consumer security; social networking sites; Facebook; LinkedIn